A PROFILE OF MORTALITY AND MORBIDITY OUTCOMES OF ILLEGAL ABORTIONS IN LAHORE - Zia, Shumaila (Journal of Postgraduate Medical Institute, 2012)
Objectives: To evaluate the morbidity, mortality and sociodemographic characteristics of illegally induced, unsafe abortion and their relationship with different modes of management. Methodology: This descriptive study was conducted in Department of Gynae/Obs; Social Security Hospital, Lahore from June 2009 - November2010. A total of 105 cases admitted in the hospital with complications of unsafe abortion that fulfilled the inclusion criteria. The patients/their female attendants were interviewed by doctors. The patients were examined in detail, investigated and managed accordingly. A structured proforma was used to collect data. The data were analyzed. Results: Out of 105 cases, 68(64.8%) were below 30 years. Eighty six (81.9%) were married and rest 19(18.1%) were unmarried females. Forty seven (44.8%) women were illiterate. About 2/3rd women were from lower socioeconomic (SE) class and 1/3rd from lower middle SE class. Only 63 patients (60.5%) were having some knowledge of contraceptives. Thirty eight (36.2%) abortions were conducted by Doctors (outside the public hospital), 34(32.4%) by untrained birth attendants and 33(31.4%) by Nurses/ lady health visitors (LHVs). Forty (38.1%) women were managed conservatively, 38(36.2%) by D&C and 27(25.7%) by laparotomy. Significantly higher number of patients (41%) underwent laparotomy whose abortion was conducted by untrained providers. Ninety five (90.5%) patients recovered while 10(9.5%) expired due to serious complications. Conclusion: Illegal abortions are more common among lower socioeconomic class and are associated with significant mortality and morbidity especially provided by unskilled providers. Further studies to assess social, cultural, legal and health system correlates are indicated.